2020
DOI: 10.1111/1750-3841.15361
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of oleogel emulsions: A comparative study between the use of recovered and commercial sunflower waxes as structuring agent

Abstract: The objective of this study was to evaluate the capacity of recovered sunflower waxes (RW) to be used as a structuring agent of oleogel emulsions in comparison with commercial sunflower waxes (CW). RW were recovered from filter cake with a simple hexane extraction procedure. For this purpose, oleogel‐based emulsions were prepared using 2%, 3.5%, and 5% w/w wax in oleogel and characterized using several physicochemical techniques in order to evaluate the potential of these materials to develop products with fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 37 publications
1
10
0
Order By: Relevance
“…In our case, we have considered SE0 as the standard. The ΔE values were found to be in the range of 4 and 12, suggesting that the color difference among the samples can be identified by the naked eye [ 50 ]. However, ΔE values of the SYL-added samples were similarly valued ( p > 0.05).…”
Section: Resultsmentioning
confidence: 99%
“…In our case, we have considered SE0 as the standard. The ΔE values were found to be in the range of 4 and 12, suggesting that the color difference among the samples can be identified by the naked eye [ 50 ]. However, ΔE values of the SYL-added samples were similarly valued ( p > 0.05).…”
Section: Resultsmentioning
confidence: 99%
“…The bright-field microscopic images suggested the formation of fiber structures which are formed through the entanglement of crystals similar to previous works ( Figure 8 ). 49 , 50 This fibrous network appearance can be due to the high content of wax esters in JFW. Analysis of the polarized light micrographs of OG revealed that spherulites or clustered crystallites were formed in OGs prepared by JFW and WGO ( Figure 9 ).…”
Section: Resultsmentioning
confidence: 99%
“…Most of the studies showed that the solid fat content of oleogels or oleogel blend (with commercial saturated fat) is relatively much lower when compared to the commercial saturated lipid systems, for example, butter, margarine, shortening and coating fat which have around 50%-90% of saturated fat. Whilst commercial saturated lipid system confers a sharp melting curve, a flat solid fat content curve was observed for oleogel under a wide range of temperature attributed to its high unsaturated fatty acid level (da Silva et al, 2018;Kim et al, 2017;Merch an Sandoval et al, 2020;Mert & Demirkesen, 2016a, Mert & Demirkesen, 2016bSi et al, 2016;Wang et al, 2021;Yılmaz & Ö gütcü, 2014Yılmaz & Ö gütcü, , 2015aYılmaz & Ö gütcü, , 2015b. Also, under most cases that oleogel tend to be less viscous and softer than the commercial solid fat further affecting the sensory attributes of the end products.…”
Section: Comparison Of Products Prepared From Classical Saturated Lip...mentioning
confidence: 99%